Biocompatibility of two model elastin‐like recombinamer‐based hydrogels formed through physical or chemical cross‐linking for various applications in tissue engineering and regenerative medicine. (26th November 2017) - Ibáñez‐Fonseca, Arturo; Ramos, Teresa L.; González de Torre, Israel; Sánchez‐Abarca, Luis Ignacio; Muntión, Sandra; Arias, Francisco Javier; del Cañizo, María Consuelo; Alonso, Matilde; Sánchez‐Guijo, Fermín; Rodríguez‐Cabello, José Carlos
Abstract: Biocompatibility studies, especially innate immunity induction, in vitro and in vivo cytotoxicity, and fibrosis, are often lacking for many novel biomaterials including recombinant protein‐based ones, such as elastin‐like recombinamers (ELRs), and has not been extensively explored in the scientific literature, in contrast to traditional biomaterials. Herein, we present the results from a set of experiments designed to elucidate the preliminary biocompatibility of 2 types of ELRs that are able to form extracellular matrix‐like hydrogels through either physical or chemical cross‐linking both of which are intended for different applications in tissue engineering and regenerative medicine. Initially, we present in vitro cytocompatibility results obtained upon culturing human umbilical vein endothelial cells on ELR substrates, showing optimal proliferation up to 9 days. Regarding in vivo cytocompatibility, luciferase‐expressing hMSCs were viable for at least 4 weeks in terms of bioluminescence emission when embedded in ELR hydrogels and injected subcutaneously into immunosuppressed mice. Furthermore, both types of ELR‐based hydrogels were injected subcutaneously in immunocompetent mice and serum TNFα, IL‐1β, IL‐4, IL‐6, and IL‐10 concentrations were measured by enzyme‐linked immunosorbent assay, confirming the lack of inflammatory response, as also observed upon macroscopic and histological evaluation. All these findings suggest that both types of ELRs possess broad biocompatibility, thus making them very promising for tissue engineering and regenerative medicine‐related applications.